THE ECOLOGICAL ROLE OF TREES AND THEIR INTERACTIONS IN FORMING THE MICROCLIMATE AMENITY OF ENVIRONMENT - Hidayat, Imawan Wahyu (Bumi Lestari; Vol 10 No 2 (2010), 2010)
Plants, especially species of trees, have an important role in modifying the microclimate, particularly temperature and humidity. This study was aimed to evaluate the effectiveness of trees in modifying the temperature and humidity and their interaction in forming the microclimate amenities. There are two methods in the study, first by comparing the temperature and humidity between open space free of shading and under the shade of tree canopies. Sample trees used as many as three trees which are Bunga Sapu tangan (Maniltoa schefferi), Bauhinia (Bauhinia purpurea), and Tanjung (Mimusops elengi). The second method is by making the observation grid which sized 50 x 50 meters that is divided into grids of smaller-sized grid of 10 x 10 meters, then analyzed the air temperature to make the isotherm lines. The study shows that trees can significantly lower the temperature (2.9-7.4 OC) and increase the humidity (0.1-3.9%). Nevertheless, the tree has a limited role and can’t stand alone in order to form microclimate amenity in the environment (THI> 26).
Keywords: microclimate, temperature, humidity, trees, amenity